Pengaruh Kualitas Pelayanan, Insentif Karyawan, Dan Pengelompokan Barang Terhadap Peningkatan Penjualan UD. Rezeki Baru Cap Rumah Adat Minang Di Kota Medan Tahun 2017-2021 - Tanjung, Ahmad Fuadi; Juliati Nasution, Yenni Samri; Tambunan, Khairina (Jurnal Manajemen Akuntansi (JUMSI), 2023)
In increasing sales there are several strategies that can be done. This study aims to determine how much direct influence variables of service quality, employee incentives, and grouping of goods to the increase in sales of UD. New Fortune Minang Traditional House Stamp At Medan City 2017-2021. The samples in this study are employees at UD. New Fortune Medan Denai District. Deep method This study used a quantitative approach using analysis the path with the linear regression model is supported by model tests and statistical tests using SPSS version 21. From the results of research conducted, the authors conclude that this research produces a coefficient of determination (R-square) that is equal to 98.4% variable Quality of service, employee incentives, and grouping of goods affect the increase in sales of UD. New Fortune Stamp Traditional House Minang in Medan City in 2017-2021, while 1.6% is explained by other factors. Simultaneously shows the variable Quality of service, Employee incentives, and grouping of goods affect the increase Sales Ud. New Fortune Minang Traditional House Stamp in Medan City Year 2017-2021, this is indicated by the value of Fcount (956.647) > Ftable (2.80). Partially shows the quality of service and grouping of goods effect on the increase in sales of UD. New Fortune Stamp Traditional House Minang in Medan City in 2017-2021, however, employee incentives are variable no effect on the increase in sales of UD. New Fortune Stamp Rumah Minang Customs in Medan City 2017-2021.